Hubungan Dukungan Keluarga dan Self Management Dengan Kepatuhan Minum Obat Pada Pasien Hipertensi di Wilayah Kerja Puskesmas Pasar Ikan Kota Bengkulu Tahun 2025 - A’izzah Al-Hasanah; Ravika Ramlis; Tita Septi Handayani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Hypertension is widely known as8a silent killer because it often develops without clear signs or symptoms, causing many individuals to be unaware of their condition. Data from Kementerian Kesehatan Republik Indonesia in 2023 indicate that only about 54.4% of patients with hypertension adhere to medication therapy as recommended by healthcare professionals. In8addition, based on8the report8of8the Survei Kesehatan8Indonesia, the prevalence8of hypertension in8Indonesia in 2023 reached 29.2%. This8study aims to analyze the8relationship8between8family support8and self management ability with medication adherence among hypertensive patients in the working area of Puskesmas Pasar Ikan Kota Bengkulu, Kota Bengkulu. This8study employed a8quantitative approach with8a cross-sectional8design. The sample8consisted of 76 respondents8diagnosed with hypertension, selected8using an accidental8sampling technique. Data8were collected through8questionnaires covering family8support, self management, and medication adherenceThe8results of the univariate8analysis showed that8most respondents8had good family support, relatively optimal self management ability, and high levels of medication adherence. The8bivariate analysis8using the8Chi-Square test8indicated a8significant relationship between8family support8and medication adherence (p-value = 0.000). Furthermore, a8significant8relationship was also found8between self-management and medication adherence among hypertensive8patients (p-value = 0.000). The findings of this study8are expected to8serve as a8basis for healthcare providers to8enhance educational programs that involve family participation and strengthen patients’ self management skills, thereby improving treatment adherence and minimizing the risk of hypertension-related complications.